2015
DOI: 10.1039/c5ra13728d
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of PtNi bimetallic nanoparticles on three-dimensional graphene for highly efficient methanol oxidation

Abstract: In the present work, platinum-nickel (PtNi) bimetallic nanoparticles with a uniform diameter of 40 nm were anchored onto a three-dimensional graphene (3DGN) by using the method of electrodeposition. The resulting PtNi/3DGN composites were developed toward highly active catalysts for methanol oxidation. Experimental results revealed that the PtNi/3DGN composites exhibited improved electrocatalytic capacity (the forward anodic peak current density of 822.1 mA/mgPt in methanol oxidation when compared with Pt alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Zhou et al reported the electrocatalytic hydrogen evolution by using 3D hierarchical MoS 2 nanosheets anchored on graphene oxide (GO), in which the better electrocatalytic performance were ascribed largely to 3D frameworks for fast charge transport and collection aa well as the synergistic effect between MoS 2 and oxygen-containing groups on GO nanosheets. Additionally, the 3D graphene frameworks embedded with Pt/Pt-based active components were also fabricated and applied for the electro-oxidation of methanol and ethanol. …”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al reported the electrocatalytic hydrogen evolution by using 3D hierarchical MoS 2 nanosheets anchored on graphene oxide (GO), in which the better electrocatalytic performance were ascribed largely to 3D frameworks for fast charge transport and collection aa well as the synergistic effect between MoS 2 and oxygen-containing groups on GO nanosheets. Additionally, the 3D graphene frameworks embedded with Pt/Pt-based active components were also fabricated and applied for the electro-oxidation of methanol and ethanol. …”
Section: Introductionmentioning
confidence: 99%
“…9, [14][15][16] PtRuNi ternary catalysts have been prepared by co-reduction of the corresponding metal precursors, however, the composition and structure of PtRuNi catalysts are rather complicated. [17][18][19][20][21] In addition, Ni species on the surface is easily to be dissolved in acidic medium in PEMFC. 22 Therefore, preparation of a core-shell structure, in which Ni species is preferred to be located inside the bulk of nanoparticles, would prevent it from dissolution in acidic medium while keeping the interaction between Ni and surface Pt.…”
Section: Introductionmentioning
confidence: 99%
“…Among bimetallic catalysts, PtNi nanoparticles (NPs) in particular are promising materials for methanol electro-oxidation since Ni is more economic than other metals [ 14 , 22 , 25 ]. PtNi catalysts with enhanced activity have been prepared by the microwave-assisted polyol reduction, and the enhancement in catalytic activity is attributed to their electronic structure modification [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of metal ions in solution is a typical approach to synthesize metal and alloy NPs [ 25 , 27 ], which often involves chemical additives and/or byproducts, such as surfactants or polymers used to stabilize metal NPs. However, the introduction of the organic materials would block the active surface of metal and alloy NPs to some extent.…”
Section: Introductionmentioning
confidence: 99%